Active Fraction Combination From Liuwei Dihuang Decoction Improves Adult Hippocampal Neurogenesis and Neurogenic Microenvironment in Cranially Irradiated Mice - Mingxiao Wei; Mingxiao Wei; Shufang Feng; Lin Zhang; Lin Zhang; Chen Wang; Shasha Chu; Tianyao Shi; Wenxia Zhou; Yongxiang Zhang; Yongxiang Zhang (Frontiers Media S.A., 2021)
Background: Cranial radiotherapy is clinically used in the treatment of brain tumours; however, the consequent cognitive and emotional dysfunctions seriously impair the life quality of patients. LW-AFC, an active fraction combination extracted from classical traditional Chinese medicine prescription Liuwei Dihuang decoction, can improve cognitive and emotional dysfunctions in many animal models; however, the protective effect of LW-AFC on cranial irradiation-induced cognitive and emotional dysfunctions has not been reported. Recent studies indicate that impairment of adult hippocampal neurogenesis (AHN) and alterations of the neurogenic microenvironment in the hippocampus constitute critical factors in cognitive and emotional dysfunctions following cranial irradiation. Here, our research further investigated the potential protective effects and mechanisms of LW-AFC on cranial irradiation-induced cognitive and emotional dysfunctions in mice.Methods: LW-AFC (1.6 g/kg) was intragastrically administered to mice for 14 days before cranial irradiation (7 Gy γ-ray). AHN was examined by quantifying the number of proliferative neural stem cells and immature neurons in the dorsal and ventral hippocampus. The contextual fear conditioning test, open field test, and tail suspension test were used to assess cognitive and emotional functions in mice. To detect the change of the neurogenic microenvironment, colorimetry and multiplex bead analysis were performed to measure the level of oxidative stress, neurotrophic and growth factors, and inflammation in the hippocampus.Results: LW-AFC exerted beneficial effects on the contextual fear memory, anxiety behaviour, and depression behaviour in irradiated mice. Moreover, LW-AFC increased the number of proliferative neural stem cells and immature neurons in the dorsal hippocampus, displaying a regional specificity of neurogenic response. For the neurogenic microenvironment, LW-AFC significantly increased the contents of superoxide dismutase, glutathione peroxidase, glutathione, and catalase and decreased the content of malondialdehyde in the hippocampus of irradiated mice, accompanied by the increase in brain-derived neurotrophic factor, insulin-like growth factor-1, and interleukin-4 content. Together, LW-AFC improved cognitive and emotional dysfunctions, promoted AHN preferentially in the dorsal hippocampus, and ameliorated disturbance in the neurogenic microenvironment in irradiated mice.Conclusion: LW-AFC ameliorates cranial irradiation-induced cognitive and emotional dysfunctions, and the underlying mechanisms are mediated by promoting AHN in the dorsal hippocampus and improving the neurogenic microenvironment. LW-AFC might be a promising therapeutic agent to treat cognitive and emotional dysfunctions in patients receiving cranial radiotherapy.